A new species of Hypsiboas from the Atlantic forest of southeastern Brazil (Amphibia : Anura : Hylidae) - Antunes, Andre Pinassi [UNESP]; Faivovich, Julian [UNESP]; Haddad, Celio Fernando Baptista [UNESP] (Amer Soc Ichthyologists & Herpetologists, 2008)
We describe a new species of Hypsiboas of the Hypsiboas pulchellus species group from highland streams of the Atlantic Forest of southeastern Brazil. Vocalizations, egg-mass, and tadpole are also described. We compared the new species with other species of the Hypsiboas pulchellus species group. The new species is most similar to Hypsiboas semiguttatus, its sister species, and Hypsiboas curupi, from which it differs in advertisement call and larval morphology. We provide information on natural history, phylogenetic relationships, embryos, geographic distribution, and conservation.